Identification of calmodulin‐like protein 5 as tumor‐suppressor gene silenced during early stage of carcinogenesis in squamous cell carcinoma of uterine cervix. Issue 6 (25th May 2021) - Kitazawa, Sohei; Takaoka, Yuki; Ueda, Yasuo; Kitazawa, Riko
Abstract: In the course of identifying the molecular mechanism that is related to strong cell‐cell adhesion in stratified structures of the squamous epithelium, calmodulin‐like protein 5 (CALML5) was identified as a spinous structure‐associated protein by producing monoclonal antibodies with the use of the crude intercellular portion of squamous tissue as an immunogen and by subsequent morphologic screening. By electrophoretic mobility shift assay (EMSA) and a series of mutagenesis studies, two transcription factors, ZNF750 and KLF4, by binding in line to the CALML5 gene promoter, were found to play a central role in CALML5 transcription. Knockdown of CALML5 by siRNA in the A431 cell line that expresses high levels of CALML5 resulted in the acceleration of wound confluence in a scratch assay, indicating that CALML5 functions as a tumor‐suppressor in uterine cervical cancer. Immunohistochemical evaluation of squamous intraepithelial lesions, carcinoma in situ (CIS) and invasive uterine cancer, revealed a reduction in CALML5 expression during the stages of CIS through various molecular pathways including the blockage of the nuclear translocation of KLF4. Conversely, restoration of the nuclear translocation of KLF4 by inhibiting ERK‐signaling reactivated CALML5 expression in ME180 cells expressing low levels of CALML5. Thus, alteration of the p63‐ZNF750‐KLF4 axis may result in critical functional loss of CALM‐related genes during cancer progression. Although the morphological association of CALML5 with the spiny‐structure in relation to cell motility is not clear, evaluation of CALML5 expression provides a useful diagnostic indicator of differentiating dysplasia, preinvasive and invasive cervical cancers.